Growth and digestive enzymes of silver catfish fed diets containing fruit residue - Lazzari R. (2019)
© 2019 Universidade Federal de Minas Gerais.In fish farming, the use of alternative ingredients has been studied, so that alternative sources can be used to minimize feed costs. This study evaluated the incorporation of grape, orange, guava, and fig residues in diets for silver catfish and its effects on growth, digestive enzymes and body composition. A total of 180 fish (initial mean weight = 22.93±0.75 g) were reared in a recirculation aquaculture system. There was no difference (P > 0.05) in the parameters of growth, dry matter, mineral matter, plasma protein, cholesterol, triglycerides, lipase, and trypsin of fish. Glucose levels were higher in fish fed diets containing fig, orange, and grape residue (P < 0.05). Lipase activity was higher in fish fed orange residue, compared to guava (P < 0.05). Diets containing guava and fig provided more body protein in silver catfish. The fish fed with diet containing orange residue had a higher content of body lipids. It can be concluded that the tested fruit residues can be used in silver catfish feeding.© 2019 Universidade Federal de Minas Gerais.Na piscicultura, o uso de ingredientes alternativos vem sendo estudado, de modo que seja possível utilizar fontes alternativas para minimizar custos com a alimentação. Neste estudo, foi avaliada a incorporação de resíduos de uva, laranja, goiaba e figo em rações para jundiá e seus efeitos no crescimento, em enzimas digestivas e na composição corporal. Foram utilizados 180 peixes (peso médio inicial = 22,93±0,75 g), criados em sistema de recirculação. Não houve diferença (P > 0.05) nos parâmetros de crescimento, matéria seca, matéria mineral, proteína plasmática, colesterol, triglicerídeos, lipase e tripsina dos peixes. Os níveis de glicose foram maiores nos peixes alimentados com dietas contendo figo, laranja e uva (P < 0.05). A atividade de lipase foi maior nos peixes alimentados com resíduo de laranja, comparado com o de goiaba (P < 0.05). As dietas contendo goiaba e figo proporcionaram mais proteína corporal nos jundiás. Os jundiás alimentados com dieta contendo resíduo de laranja apresentaram maior teor de lipídeos corporal. Conclui-se que os resíduos de frutas testados podem ser usados na alimentação do jundiá.